Perumusan dokumentasi keperawatan berbasis pedoman SDKI, SLKI dan SIKI di IGD RS tipe B Kota Malang - Wahyuningsih, Indri; Anggraini, Ika Rizki (JOURNAL of Public Health Concerns, 2025)
Background: Nursing documentation serves as evidence of responsibility and legal protection for nurses in carrying out their duties. This documentation serves as an authentic record of the implementation of professional nursing care and can therefore be used as a basis for accountability for all actions taken by nurses. Should legal issues arise related to the nursing profession, complete and accurate documentation can serve as valid evidence in court. However, inadequate nursing documentation remains an internationally recognized problem in healthcare. In emergency nursing, which requires a fast-paced, high-pressure work environment that can determine the life or death of a patient in a matter of minutes, nurses are required to possess high competency to carry out the nursing process skillfully, precisely, and accurately. In addition to providing immediate action, emergency nurses are also required to create complete, accurate, and legally compliant nursing records. Purpose: To formulate nursing documentation based on the Indonesian Nursing Diagnosis Standards (INDS), the Indonesian Nursing Outcome Standards (INOS), and the Indonesian Nursing Intervention Standards (INIS) in the emergency department (ER). Method: This community service activity began in December 2024, focusing on developing nursing documentation in accordance with the INDS, INOS and INIS standards in the Emergency Room. The process was carried out through collaboration between the community service team, emergency room nurses, and nursing students. This activity included observation and subsequent discussion of the systematics and documentation models applied in the emergency room. The next stage included a lecture presentation to explain the documentation model and create a nursing documentation form template, coordination with emergency room nurses, and designing an initial nursing record format appropriate to the needs of emergency services. Results: The nursing documentation used was a mixture of manual and electronic formats, did not fully adhere to the INDS, INOS and INIS, and contained irregularities in the writing of nursing documentation. The community service team, along with partners, successfully identified the 10 most frequently encountered medical diagnoses in the emergency room at UMM Hospital and used these as the basis for developing a standardized nursing documentation form that integrates elements of the INDS, INOS and INIS. Conclusion: The community service program ran well and had a positive impact on improving nurses' knowledge in applying and documenting the INDS, INOS and INIS guidelines in the emergency department (ER). Suggestion: Future activities can be more applicable and conducted sustainably. Sustainable mentoring activities in preparing nursing documentation based on the INDS, INOS and INIS can be integrated with the Hospital Management Information System (MIS). Keywords: Documentation; Emergency department; INDS; INIS; INOS; Nursing process Pendahuluan: Dokumentasi keperawatan berfungsi sebagai bukti tanggung jawab dan perlindungan hukum bagi perawat dalam menjalankan tugasnya. Dokumentasi ini merupakan catatan autentik dari pelaksanaan asuhan keperawatan profesional, sehingga dapat digunakan sebagai dasar pertanggungjawaban atas seluruh tindakan yang dilakukan perawat. Apabila terjadi masalah hukum terkait profesi keperawatan, dokumentasi yang lengkap dan akurat dapat menjadi bukti yang sah di pengadilan. Namun, dokumentasi keperawatan yang kurang memadai masih menjadi masalah yang diakui secara internasional pada layanan kesehatan. Pada keperawatan gawat darurat yang memiliki lingkungan kerja cepat, penuh tekanan, dan dapat menentukan hidup-matinya pasien dalam hitungan menit, perawat dituntut memiliki kompetensi tinggi untuk melaksanakan proses keperawatan secara terampil, tepat, dan akurat. Selain memberikan tindakan segera, perawat gawat darurat juga diwajibkan membuat catatan keperawatan yang lengkap, tepat, dan sesuai ketentuan hukum. Tujuan: Merumuskan dokumentasi keperawatan berdasarkan Standar Diagnosa Keperawatan Indonesia (SDKI), Standar Luaran Keperawatan Indonesia (SLKI), dan Standar Intervensi Keperawatan Indonesia (SIKI) di instalasi gawat darurat (IGD). Metode: Kegiatan pengabdian kepada masyarakat ini dimulai pada bulan Desember 2024 dengan fokus pengembangan dokumentasi keperawatan sesuai standar SDKI, SLKI, dan SIKI di IGD. Proses dilaksanakan melalui kolaborasi antara tim pengabdian, perawat IGD, dan mahasiswa keperawatan. Dalam kegiatan ini adalah melakukan observasi dan selanjutnya menelaah dengan berdiskusi mengenai terhadap sistematika dan model dokumentasi yang telah di aplikasikan di IGD. Tahap berikutnya adalah melakukan presentasi dengan metode ceramah untuk memaparkan secara sederhana model pendokumentasian dan pembuatan template formulir dokumentasi keperawatan, koordinasi dengan perawat IGD, dan perancangan format awal catatan keperawatan yang sesuai dengan kebutuhan layanan gawat darurat. Hasil: Menunjukkan bahwa dokumentasi keperawatan yang digunakan masih bersifat campuran antara format manual dan elektronik, belum sepenuhnya mengacu pada SDKI, SLKI, dan SIKI serta terdapat ketidakteraturan dalam penulisan dokumentasi keperawatan. Tim pengabdian bersama mitra berhasil mengidentifikasi 10 diagnosis medis yang paling sering ditemukan di IGD RS UMM dan menjadikannya dasar penyusunan formulir dokumentasi keperawatan terstandar yang mengintegrasikan elemen SDKI, SLKI, dan SIKI. Simpulan: Program pengabdian masyarakat berjalan dengan baik dan memberikan dampak positif terhadap peningkatan pengetahuan perawat dalam mengaplikasikan dan melakukan dokumentasi menggunakan pedoman SDKI, SLKI dan SIKI di instalasi gawat darurat (IGD). Saran: Pelaksanaan kegiatan selanjutnya bisa lebih aplikatif dan dilakukan secara berkesinambungan. Keberlanjutan kegiatan pendampingan dalam penyusunan dokumentasi keperawatan berbasis SDKI, SLKI dan SIKI dapat diintegrasikan dengan SIM RS.